Semi-Interpenetrating Polymer Networks Based on N-isopropylacrylamide and 2-acrylamido-2-methylpropane Sulfonic Acid for Intramolecular Force-Compensated Sensors. Issue 16 (6th January 2021) - Binder, Simon; Zschoche, Stefan; Voit, Brigitte; Gerlach, Gerald
Abstract : Stimulus-responsive hydrogels are swellable polymers that take up a specific volume depending on a measured variable present in solution. Hydrogel-based chemical sensors make use of this ability by converting the resulting swelling pressure, which depends on the measured variable, into an electrical value. Due to the tedious swelling processes, the measuring method of intramolecular force compensation is used to suppress these swelling processes and, thus, significantly increase the sensor's response time. However, intramolecular force compensation requires a bisensitive hydrogel. In addition to the sensitivity of the measured variable the gel has to provide a second sensitivity for intrinsic compensation of the swelling pressure. At the same time, this hydrogel has to meet further requirements, e.g. high compressive strength. Until now, interpenetrating polymer networks (IPN) have been used for such a force-compensatory effective hydrogel, which are complex to manufacture. In order to significantly simplify the sensor design and production, a simpler synthesis of the bisensitive hydrogel is desirable. This paper presents a new bisensitive hydrogel based on semi-interpenetrating polymer networks. It is based on a copolymer network consisting of N -isopropylacrylamide (NiPAAm) and 2-acrylamido-2-methylpropane sulfonic acid (AMPS) and long PAMPS strands that permeate it. Measurements show, that this hydrogel meets all essential requirements for intramolecular force compensation and is at the same time much easier to synthesize than previously used IPN hydrogels.